Traumatic Dissections of Bilateral Internal carotid Artery with Aneurysms Formation. Issue 5 (September 2016) - Chang, CS; Tsai, IT; Liang, CY; Hsu, CW
Carotid artery dissection is an unusual complication of blunt neck trauma with high mortality and severe neurological deficits. Traumatic bilateral dissections and dissecting aneurysms are extremely rare. A 17-year-old male presented to our emergency department with sudden onset of right hemiparesis and aphasia. Initial computed tomography scan of head and neck showed no remarkable finding. On the second day, a magnetic resonance angiography of head and neck demonstrated bilateral extracranial internal carotid artery dissections. The diagnosis of traumatic carotid artery dissection for emergency physicians is difficult because of the absence or delayed onset in symptomatology. Magnetic resonance angiography is currently considered as an appropriate initial diagnostic tool for carotid artery injury. In clinical practice, early diagnosis by keeping a high index of suspicions is required by emergency physicians.